A copper-based metal–organic framework decorated with electrodeposited Fe2O3 nanoparticles for electrochemical nitrite sensing - Amali, R. K. A.; Lim, H. N.; Ibrahim, I.; Zainal, Z.; Ahmad, S. A. A. (Springer, 2022)
An amperometric nitrite sensor is reported based on a screen-printed carbon electrode (SPCE) modified with copper(II)-benzene-1,4-dicarboxylate (Cu-BDC) frameworks and iron(III) oxide nanoparticles (Fe2O3 NPs). First, copper(I) oxide (Cu2O) nanocubes were synthesized, followed by a solvothermal reaction between Cu2O and H2BDC to form square plate-like Cu-BDC frameworks. Then, Fe2O3 NPs were electrodeposited on Cu-BDC frameworks using a potentiostatic method. The Fe2O3@Cu-BDC nanocomposite benefits from high conductivity and large active surface area, offering excellent electrocatalytic activity for nitrite oxidation. Under optimal amperometric conditions (0.55 V vs. Ag/AgCl), the sensor has a linear range of 1 to 2000 µM with a detection limit of 0.074 µM (S/N = 3) and sensitivity of 220.59 µA mM−1 cm−2. The sensor also provides good selectivity and reproducibility (RSD = 1.91%, n = 5). Furthermore, the sensor exhibits long-term stability, retaining 91.4% of its original current after 4 weeks of storage at room temperature. Finally, assessing nitrite in tap and mineral water samples revealed that the Fe2O3@Cu-BDC/SPCE has a promising prospect in amperometric nitrite detection.